Formulación estratégica. Caso: empresas del sector alimentos y bebidas del estado Carabobo - Cordero Borjas, Ana Emilia (2011)
The purpose of this paper is to analyze the strategic process of a group of companies in the food and beverage sector of Carabobo State, Venezuela. To achieve it a non-experimental study was conducted with special emphasis on transectional descriptive design and an instrument was applied to a non probabilistic sample taken from eleven organizations of the food and beverage manufacturing industry in the Carabobo State, Venezuela. We concluded that in the group there is no clear trend or identification with respect to some of the schools of strategic thought, in particular, as regards to the strategic process; that is to say, there is not enough uniformity in the responses to identify which school of strategic thought (from the application of its premises) has a greater presence in some of the companies. Considering the prismatic nature of the strategic process, it can be said that the schools with more influence at the time of making the strategic formulation are Planning, Positioning, Cultural, Environmental and Configuration.